Quantitative Lesion-to-Fat Elasticity Ratio Measured by Shear-Wave Elastography for Breast Mass: Which Area Should Be Selected as the Fat Reference? - Youk, Ji Hyun (PLoS One, 2015)
OBJECTIVES: To investigate whether the diagnostic performance of lesion-to-fat elasticity ratio (E(ratio)) was affected by the location of the reference fat. METHODS: For 257 breast masses in 250 women who underwent shear-wave elastography before biopsy or surgery, multiple E(ratio)s were measured with a fixed region-of-interest (ROI) in the mass along with multiple ROIs over the surrounding fat in different locations. Logistic regression analysis was used to determine that E(ratio) was independently associated with malignancy adjusted for the location of fat ROI (depth, laterality, and distance from lesion or skin). Mean (E(mean)) and maximum (E(max)) elasticity values of fat were divided into four groups according to their interquartile ranges. Diagnostic performance of each group was evaluated using the area under the ROC curve (AUC). False diagnoses of E(ratio) were reviewed for ROIs on areas showing artifactual high or low stiffness and analyzed by logistic regression analysis to determine variables (associated palpable abnormality, lesion size, the vertical distance from fat ROI to skin, and elasticity values of lesion or fat) independently associated with false results. RESULTS: E(ratio) was independently associated with malignancy adjusted for the location of fat ROI (P<0.0001). Among four groups of fat elasticity values, the AUC showed no significant difference (<25th percentile, 25th percentile~median, median~75th percentile, and ≥75th percentile; 0.973, 0.982, 0.967, and 0.954 for E(mean); 0.977, 0.967, 0.966, and 0.957 for E(max)). Fat elasticity values were independently associated with false results of E(ratio) with the cut-off of 3.18 from ROC curve (P<0.0001). ROIs were set on fat showing artifactual high stiffness in 90% of 10 false negatives and on lesion showing vertical striped artifact or fat showing artifactual low stiffness in 77.5% of 71 false positives. CONCLUSION: E(ratio) shows good diagnostic performance regardless of the location of reference fat, except when it is placed in areas of artifacts.